Uma medida de pobreza energética para o Brasil - Moreira, Rogério Silva (2023)
One of the UN Sustainable Development Goals is to ensure, by 2030, universal access to affordable, reliable and modern energy services. In this sense, the present study analyzed energy poverty in Brazil, using the Multidimensional Energy Poverty Index (IPEM) developed by Nussbaumer, Bazilian and Modi (2012). A Logistic Regression was estimated in order to investigate the determinants of the incidence of multidimensional energy poverty among Brazilian households. The information comes from the Household Budget Survey - POF 2017/2018. Additionally, social inequality in energy poverty was verified through the concentration curve (CC) and the concentration index (CI). The estimated IPEM for Brazil was 0.107, indicating a low level of energy poverty. The absence of a computer is the indicator that most contributes to the multidimensional energy poverty index (41.2%), followed by the absence of a fan (27.9%) and the use of inappropriate fuels for cooking (24.7%). The results indicated a greater concentration of energy poverty among the poorest part of the population. In addition, families living in a situation of multidimensional energy poverty suffer from various household deprivations, which further aggravates their situation of social vulnerability.